IDENTIFIKASI DEKSAMETASON DALAM JAMU PEGAL LINU SEDIAAN SERBUK YANG BEREDAR DI PASAR-PASAR KOTA BANDAR LAMPUNG SECARA KROMATOGRAFI LAPIS TIPIS - Sudewi Mukaromah Khoirunnisa (Journal of Science and Applicative Technology, 2017)
A total of 26.6% of the population in Lampung Province consume traditional medicine, one of which is Jamu Pegal Linu. However, a large public interest in herbal products is often misused by herbal manufacturers that it is possible to add BKO (Medicinal Chemicals), such as dexamethasone.The purpose of this study is to identify the presence or absence of dexamethasone in the preparation of Jamu Pegal Linu. The samples are taken from the store and depot herbs contained in the Markets of Bandar Lampung, acquired three different brands. The method used is Thin Layer Chromatography using dikloretan motion: diethyl ether: methanol: water (77:15: 8: 1,2) as a mobile phase which are non-polar, and silica gel GF 254nm as a stationary phase. The result showed that the detection of three samples of Jamu Pegal Linu contained staining purple and the difference of Rf sample with reference standard on the first repetition is 0.46, 0.44, 0.47, and on the second repetition is 0.45, 0.45 and 0.48, which are â‰¥ 0.05. It can be concluded that the sample of Jamu Pegal Linu in Bandar Lampung 0% containing dexamethasone.